Cultural values, status signalling and quiet luxury adoption in collectivist emerging markets - Cut Kesuma Pahlufi; Muhammad Dharma Tuah Putra Nasution (International Journal of Economics, Business Management and Accounting (IJEBMA), 2026)
Purpose: Existing status signalling frameworks, developed within individualistic cultural contexts, cannot predict luxury consumption in collectivist societies, where affluent consumers favour understated expressions despite possessing both the economic means and the social motivation to signal status conspicuously.Design/methodology/approach: We develop Cultural Signalling Adaptation Theory by integrating status signalling theory, cultural values research, and acculturation mechanisms, illustrated through Indonesia as a collectivist emerging market case study.Findings: The framework identifies four mechanisms through which cultural values reshape luxury signalling: cultural filtering, which suppresses materialist motivation; identity protection, which generates resistance to culturally incongruent consumption; bicultural competence, which enables navigation between global sophistication Research limitations/implications: The framework is conceptual and requires empirical validation across diverse collectivist markets. Priority directions include scale development for cultural adaptation strategies, boundary condition testing across Southeast and South Asian contexts, and longitudinal tracking of adaptation patterns.Practical implications: Luxury brands should emphasise cultural sensitivity, quality craftsmanship, and community-oriented positioning over status symbolism, with segmentation based on cultural adaptation approaches rather than economic capability alone.         Originality/value: This paper extends signalling theory beyond individualistic assumptions by demonstrating cultural moderation of the wealth-status relationship